Semi-insulating GaAs based detector of fast neutrons produced by D–T nuclear reaction. (1st December 2016) - Šagátová, A.; Kubanda, D.; Zat'ko, B.; Sedlačková, K.; Nečas, V.; Solar, M.; Granja, C.
Abstract: We have examined semi-insulating (SI) GaAs detectors with high density polyethylene (HDPE) conversion layer by a mono-energetic neutrons with kinetic energy of 16.755 MeV generated by a deuterium—tritium nuclear reaction. First, the influence of HDPE layer thickness on the relative detection efficiency of fast neutrons was studied. The MCNPX (Monte Carlo N-particle eXtended) code has been used to support the analysis of the experiment. The theoretical optimum thickness of the conversion layer was determined to 1.9 mm using the MCNPX code. The HDPE conversion layers of various thicknesses, in the range from 50 μ  m to 3200 μ  m, were glued on the top Schottky contact of SI GaAs detector in the experiment. The neutron detection efficiency was evaluated from measured spectra and compared to results from simulations. The experimental data showed very good agreement with simulation results. Then the effect of active detector thickness modified by detector reverse bias on neutron detection efficiency was studied. Finally, the effect of the angle of irradiation on neutron detection efficiency was evaluated exhibiting decreasing tendency with increasing deviation from perpendicular direction of impinging neutrons.